Assessing the impact of time windows on last-mile sustainability: A scoreboard-based approach and case study analysis - Iria González-Romero; Juan Bastero-Sellán; J. Carlos Prado-Prado (Journal of Industrial Engineering and Management)
Purpose: To ensure customer satisfaction, e-retailers have focused on providing a last-mile service that includes time windows. Due to the sustainable challenge this posed, the purpose of this article is to define a method that can be used to evaluate the impact of time windows on sustainability and to apply this method to a particular case study.